2002
DOI: 10.1074/jbc.m201584200
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Sterol Regulatory Element-binding Protein-1 (SREBP-1) Ameliorates Fatty Livers but Not Obesity or Insulin Resistance in Lep/Lep Mice

Abstract: Obesity is a common nutritional problem often associated with diabetes, insulin resistance, and fatty liver (excess fat deposition in liver). Leptin-deficient Lep ob / Lep ob mice develop obesity and those obesity-related syndromes. Increased lipogenesis in both liver and adipose tissue of these mice has been suggested. We have previously shown that the transcription factor sterol regulatory element-binding protein-1 (SREBP-1) plays a crucial role in the regulation of lipogenesis in vivo. To explore the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
224
4
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 338 publications
(254 citation statements)
references
References 37 publications
22
224
4
4
Order By: Relevance
“…Ectopic expression of a constitutively active SREBP1c surprisingly conferred lipodystrophy in mice . Other in vivo studies with a double-mutant leptin-deficient ob/ob mice and SREBP-1 2/2 mice suggested that SREBP-1 was not needed for adipose tissue expansion (Yahagi et al 2002). Overall, the data suggest that although there is in vitro evidence to show SREBP-1 is required for adipocyte differentiation, the in vivo studies consistently show that SREBP-1 expression is not critical for adipose tissue development and/or expansion.…”
Section: Srebp-1mentioning
confidence: 58%
“…Ectopic expression of a constitutively active SREBP1c surprisingly conferred lipodystrophy in mice . Other in vivo studies with a double-mutant leptin-deficient ob/ob mice and SREBP-1 2/2 mice suggested that SREBP-1 was not needed for adipose tissue expansion (Yahagi et al 2002). Overall, the data suggest that although there is in vitro evidence to show SREBP-1 is required for adipocyte differentiation, the in vivo studies consistently show that SREBP-1 expression is not critical for adipose tissue development and/or expansion.…”
Section: Srebp-1mentioning
confidence: 58%
“…There is strong evidence that downregulation of SCD1 prevents or reduces the development of NAFLD, obesity and insulin resistance [29][30][31][32]. Elevated hepatic transcription of Scd1 has been reported in fat-fed mice of the 129S6 [13] and C57BL/6J [13,23] strains.…”
Section: Discussionmentioning
confidence: 99%
“…ob/ob mice (42). Mice lacking the VLDLR exhibit normal lipid levels and a modest decrease in epididymal adipose tissue weights and are protected from diet-induced obesity (43,44).…”
Section: Discussionmentioning
confidence: 99%